Structural changes in the beef meat demand in Slovakia and demand elasticity estimation - D. Hupková; P. Bielik; N. Turčeková (Agricultural Economics (AGRICECON), 2009)
The article focuses on assessing the consumer habits attitudes and behaviour towards the beef meat demand. The main objective of this study is to investigate the determinants of the households' beef meat consumption using the main economic factors. Determining and analysis of consumer behaviour on the individual household categories level and the subsequent comparison of impact factors on consumer decision will give us an assumption to the complex understanding of the consumer behaviour determinants. We used panel data to estimate the beef meat demand in Slovakia. The data were obtained from the Household Budget Survey of the Slovak Statistical Office. The estimates of price and income elasticities of the beef meat demand are also obtained. The results indicate that the food patterns development in Slovakia during the past two decades has undergone rapid structural changes. The declining beef meat consumption is influenced mainly by the decreasing purchasing power and the occurrence of the BSE disease. According to the elasticity estimation results, we can state that the beef meat demand is price and income inelastic. Key words: beef meat consumption, households' consumption, price elasticity, income elasticity. BSE disease